2021
DOI: 10.1038/s41598-021-92894-6
|View full text |Cite
|
Sign up to set email alerts
|

Improving wheat grain yield via promotion of water and nitrogen utilization in arid areas

Abstract: Crop yield is limited by water and nitrogen (N) availability. However, in Hexi Corridor of northwestern China, water scarcity and excessive fertilizer N in wheat (Triticum aestivum L.) production causes serious conflicts between water and N supply and crop demand. A field experiment was conducted from 2016 to 2018 to evaluate whether reducing of irrigation and fertilizer N will reduce grain yield of wheat. There were two irrigation quotas (192 and 240 mm) and three fertilizer N rates (135, 180, and 225 kg N ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 52 publications
2
12
0
Order By: Relevance
“…All plants in each plot were harvested after crop maturation. Air-dried GY (kg ha −1 ) was obtained in each plot and weighed 43 , and ear length (EL), ear diameter (ED), kernel number per ear (KN), and 100-kernel weight (KW) were determined.…”
Section: Methodsmentioning
confidence: 99%
“…All plants in each plot were harvested after crop maturation. Air-dried GY (kg ha −1 ) was obtained in each plot and weighed 43 , and ear length (EL), ear diameter (ED), kernel number per ear (KN), and 100-kernel weight (KW) were determined.…”
Section: Methodsmentioning
confidence: 99%
“…Similar results by Abedi et al (2011) reported that higher grain yield was obtained under treatment with 240 kg N ha -1 (Optimum N) as compared to 120 kg N ha -1 (lower N), and 360 kg N ha -1 (Higher N). Tan et al (2021) observed the wheat production and performance under three fertilizers N rates (135, 180, and 225 kg N ha -1 ) with two irrigation quotas and concluded that wheat production was higher under the optimum dose of fertilizer N rate at 180 kg N ha −1 .…”
Section: Effect Of Different Nitrogen and Phosphorous Dose On Yield A...mentioning
confidence: 99%
“…Water use efficiency (WUE) is an important indicator for assessing crop productivity, and the increase in wheat yield is highly dependent on water and nutrient supply. In general, an appropriate irrigation and fertilizer strategy can improve WUE, maintaining the crop yield (Tan et al, 2021). However, Wang et al (2017) found increased crop evapotranspiration (ET) at higher fertilizer application, which reduced crop yield and WUE.…”
Section: Core Ideasmentioning
confidence: 99%